Shape Adjustment of a Large Planar Phased Array Antenna With Nonlinear Cable Actuators - Jiyang Zhou; Xiang Liu; Guoping Cai; Jun Sun; Dongfang Zhu (International Journal of Aerospace Engineering)
Shape adjustment of large planar phased array antennas is significant because the shape distortion of phased arrays can greatly reduce the antenna’s gain in the observing direction. This study selects the inherent diagonal cables driven by motors as actuators, initially used to improve the stiffness of the antenna structure. The shape adjustment can be implemented by changing the length of the diagonal cables, so that there is no need to design additional control devices, which can significantly reduce the mass and improve the reliability of the antenna system. For shape adjustment, the cable tensions are chosen as the control inputs in general, but for structures with finite deformations, the cable tensions may be strongly coupled and therefore can no longer be used as the control inputs. We examine all the sources of the elongation of the cable actuator and group them into three categories: pre-elongation, passive elongation, and feedback elongation. Since the feedback elongations of different cables are driven independently by the motors and do not change with the structural deformation, they can be used as the control inputs. Giving a detailed theoretical derivation, this paper demonstrates the necessity of considering nonlinearity of the cable actuator and proposes a nonlinear model of the active cable element. Further, an optimization model is established for shape adjustment, and the genetic algorithm is used to solve this problem. The effectiveness of the proposed nonlinear active cable element and the shape adjustment method is validated by simulations. Results show that the shape adjustment can be successfully achieved by the nonlinear cable actuators proposed in this paper. Moreover, the effect of pre-elongation on the stiffness of the antenna structure can be well reflected by the nonlinear cable actuators, and the relationship between the shape adjustment and the number of actuators is also investigated.